The Students’ Problems and Solutions in Writing an Argumentative Essay on Gender Issue - Lestari Setyowati; Fadiah Agustina; Sony Sukmawan; Ana Ahsana El-Sulukiyyah; Barotun Mabaroh (Yayasan Visi Intan Permata, 2020)
This study is intended to find out the students’ problems and their solutions in writing argumentative essays. The subjects of this study were the fourth-semester students of English Education study program, Faculty of Pedagogy and Psychology, University of PGRI Wiranegara in the academic year 2019-2020. This study used Byrne’s classification in 1995 about writing problems, namely psychological, linguistic, and cognitive. This uses descriptive quantitative design. The instruments were documentation of the students’ writing tasks and interviews. The result shows the almost all students have no problems in making thesis statements and refutations for their argumentative essay regarding gender issue. The students’ psychological problems are anxiety, nervousness, the feeling of pressure in timed writing and perfect work, a negative expectation in writing, and low self-confidence. For the linguistic problems, the result from both data indicated that students faced problems in tenses, word-class, word formation, the use of the article, and word error. While the cognitive problems faced by the students are being ignorant in the use of punctuation, short knowledge in giving appropriate examples and details in the body of the essay, and lack of knowledge in writing reference. The solutions proposed by the students, among others are to have more readings on the topic, to be self-motivated learners, to propose untimed writing to the lecturer, and to use writing tools applications.